1994
DOI: 10.1139/x94-050
|View full text |Cite
|
Sign up to set email alerts
|

Heritabilities and additive genetic coefficients of variation in forest trees

Abstract: Estimates of individual-tree narrow-sense heritability and additive genetic coefficient of variation of seven traits of forest trees were compiled from 67 published papers. Distributions of the values for each trait were characterized and compared by calculating medians and running Kolmogorov–Smirnov and Wilcoxon signed-rank tests. Generalizations are possible about at least some of the traits examined. Heritability of wood specific gravity was almost always above 0.3 (median 0.48). Heritabilities for other tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
114
4
20

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(169 citation statements)
references
References 0 publications
31
114
4
20
Order By: Relevance
“…CV G for wood density was rather low. However, its values were similar to those found in other studies for height growth [5]. In the present study, the CV G for wood density of cumulated rings was rather stable over the 10-year period of the study at almost all sites.…”
Section: Age Trends In Clonal Variation and Repeatabilitysupporting
confidence: 92%
“…CV G for wood density was rather low. However, its values were similar to those found in other studies for height growth [5]. In the present study, the CV G for wood density of cumulated rings was rather stable over the 10-year period of the study at almost all sites.…”
Section: Age Trends In Clonal Variation and Repeatabilitysupporting
confidence: 92%
“…Barnes et al (1992) reported that heritability estimates are often inflated by selective thinning if there are dominance effects present. Wood quality traits are usually under strong additive genetic control (Cornelius, 1994;Raymond, 2002) while dominance effects can be significant in the genetic control of growth traits in eucalypts (Bouvet et al, 2009). Therefore, selective thinning for growth should have had little effect on heritability of wood density and cellulose content.…”
Section: Effect Of Thinning and Sampling Methods On Heritabilities Andmentioning
confidence: 99%
“…This variation is used in forest tree breeding programs to select and create new genotypes (Kremer, 1986;Cornelius, 1994 (Cown, 1981) and in forest tree breeding programs (Villeneuve et al, 1987;Chantre et al, 1992;Adams et al, 1993 (Hoffmeyer, 1978(Hoffmeyer, , 1979Cown, 1981 …”
mentioning
confidence: 99%